Quantitative evaluation of hemodynamic parameters by echocardiography in patients with post-cardiotomy cardiac shock supported by extracorporeal membrane oxygenation - Fuyong Ye; Yuwen Yang; Yinting Liang; Jianhua Liu (Journal of Cardiothoracic Surgery, 2023)
Abstract Background When drugs fail to reverse post-cardiotomy cardiac shock (PCS), extracorporeal membrane oxygenation (ECMO) is considered the most effective adjuvant strategy. Transthoracic echocardiography is a useful imaging modality for monitoring of cardiac hemodynamics. The aim of this study was to investigate the value of echocardiography for monitoring the left and right heart hemodynamics in PCS patients before, during, and after weaning from ECMO. Methods Fifty-two patients were divided into successful weaning group (group A, n = 23) and non-successful weaning group (group B, n = 29). Hemodynamic parameters measured by echocardiography were collected before, during, and after ECMO. The intra-group changes and inter-group differences were retrospectively analyzed. Results In group A, the central venous pressure (CVP), proximal right ventricular outflow tract (RVOT), tricuspid annular plane systolic excursion (TAPSE), velocity of tricuspid valve (TVDV), and systolic velocity of tricuspid annulus ( $${\text{s}}_{{{\text{TV}}}}^{{′ }}$$ s TV ′ ) during ECMO were significantly lower than those before ECMO. After ECMO, left ventricular ejection fraction (LVEF), systolic velocity of mitral annulus ( $${\text{s}}_{{{\text{MV}}}}^{{′ }}$$ s MV ′ ), and velocity–time integral of LV outflow tract (LVOT-VTI) were higher than pre-ECMO levels, and CVP, LVEF, $${\text{s}}_{{{\text{MV}}}}^{{′ }}$$ s MV ′ , LVOT-VTI, RVOT, TAPSE, TVDV and $${\text{s}}_{{{\text{TV}}}}^{{′ }}$$ s TV ′ were higher than those during ECMO (all P < 0.05). In group B, compared to pre-ECMO, subjects exhibited decreased CVP, RVOT, TAPSE, TVDV and $${\text{s}}_{{{\text{TV}}}}^{{′ }}$$ s TV ′ during ECMO. TAPSE, TVDV, and $${\text{s}}_{{{\text{TV}}}}^{{′ }}$$ s TV ′ were continuously lower after ECMO, while CVP and RVOT increased after ECMO (all P < 0.05). After ECMO, LVEF, $${\text{s}}_{{{\text{MV}}}}^{{′ }}$$ s MV ′ , LVOT-VTI, TAPSE, TVDV and $${\text{s}}_{{{\text{TV}}}}^{{′ }}$$ s TV ′ in group A were higher than those in group B (all P < 0.05). Inter-group comparison showed the LVEF and RV Tei indices of group A were significantly different than those of group B before, during, and after ECMO. Conclusion Quantitative assessment of both LV and RV by echocardiography is important for ECMO weaning. Patients with better LVEF and lower RV Tei index may have a better chance of successful weaning from ECMO.